Large Multinodular Toxic Goiter: Is Surgery Always Necessary? - Roberto Negro; Gabriele Greco (Case Reports in Endocrinology)
Patients suffering from multinodular toxic goiter (MNTG) are candidates to thyroidectomy or radioiodine 131I (131I) therapy. Thyroidectomy may be preferable especially when the volume of hyperfunctioning tissue is so large that a single administration of 131I is unlikely to cure the patient in terms of nodule’s volume reduction and thyroid function. We describe the case of a 71-year-old man suffering from thyrotoxic state for the presence of two large hyperfunctioning thyroid nodules. As the patient refused surgery, at first we administered 600 MBq dose of 131I, which was unable to solve hyperthyroidism and local compressive symptoms. Then, before administering another 131I dose, the patient underwent a laser ablation treatment (LAT) in both nodules. After a significant shrinkage due to LAT, the patient received 400 MBq 131I. This procedure was able to definitely cure hyperthyroidism, to induce a significant reduction of nodules’ volume, and to render the patient asymptomatic for compressive symptoms. This case demonstrates that 131I preceded by LAT represents a valid alternative strategy to surgery, even in the presence of two large coexistent hot nodules.